(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
Foreign investments play a significant role in the development of the national economy. They bring not only financial resources but also innovation, technology, and managerial expertise. The effective attraction of these investments is directly linked to the legal and economic conditions established by the state. In Uzbekistan, measures to support foreign investors include tax and financial incentives, investment legislation, free economic zones, and public-private partnership mechanisms. These initiatives create opportunities for job creation, enhancing export potential, and promoting technological modernization in the country. At the same time, ensuring the stability of legal guarantees, reducing bureaucratic barriers, and protecting investors’ rights are essential for securing long-term inflows of foreign capital.